2022
DOI: 10.3390/biom12010146
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the lncRNA MALAT1 in Neuroprotection against Hypoxic/Ischemic Injury

Abstract: Hypoxic and ischemic brain injury can cause neurological disability and mortality, and has become a serious public health problem worldwide. Long-chain non-coding RNAs are involved in the regulation of many diseases. Metastasis-related lung adenocarcinoma transcript 1 (MALAT1) is a type of long non-coding RNA (lncRNA), known as long intergenic non-coding RNA (lincRNA), and is highly abundant in the nervous system. The enrichment of MALAT1 in the brain indicates that it may be associated with important function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Previous studies have revealed that Malat1 ln-cRNA could be a potential biomarker for the diagnosis as well as prognosis of atherosclerotic cardiovascular disease [4], cancer [5][6][7][8], multiple sclerosis [9], and sepsis [10]. Different experimental and clinical research has shown the anti-inflammatory and anti-apoptotic roles of Malat1 in the brain [11][12][13]. The downregulation of lncRNA Malat1 in IS patients has been reported in previous studies [12,14].…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies have revealed that Malat1 ln-cRNA could be a potential biomarker for the diagnosis as well as prognosis of atherosclerotic cardiovascular disease [4], cancer [5][6][7][8], multiple sclerosis [9], and sepsis [10]. Different experimental and clinical research has shown the anti-inflammatory and anti-apoptotic roles of Malat1 in the brain [11][12][13]. The downregulation of lncRNA Malat1 in IS patients has been reported in previous studies [12,14].…”
Section: Introductionmentioning
confidence: 67%
“…Some recent studies have reported that lncRNAs such as MEG3, MALAT1, and SNHG1 are involved in the initiation and progression of PD 39 . There is plenty of MALAT1 in the brain, which is essential for controlling synaptic density 69 . Based on the findings of this research, in the Par group, the expression of MALAT1 decreased in ST and PBMS.…”
Section: Discussionmentioning
confidence: 99%
“…Malat1 is known as a long intergenic noncoding RNA and is highly abundant in the nervous system. Accumulating evidence has indicated that this lncRNA plays vital roles in regulating various physiological processes, including apoptosis, autophagy, immune and inflammatory responses, and endothelial dysfunction of ischemic stroke ( Wang et al, 2022 ). The expression of Malat1 was also found to be upregulated in ischemic stroke, while its downregulation was shown to improve the neurological deficit score and reduce neuronal apoptosis and the size of cerebral infarction by regulating miR-211-5p to in turn regulate the expression of COX-2 ( Tan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%